High rate of diabetes in the Asia-Pacific Island: Possible role of rapid urbanization A hospital based study (South East Asia Journal of Public Health, 2017)
Asia-Pacific countries are experiencing lifestyle-related non-communicable disease crises. Kimbe, one of Papua New Guineas provincial capitals is noted as the fastest growing city in the South Pacific subcontinent yet its impact on diabetes mellitus (DM) is not known. To determine pattern of newly diagnosed DM, we conducted a retrospective review of Kimbe General Hospital medical admissions from January 2009 to December 2012. 125 patients were diagnosed with diabetes with male: female ratio of 1.1: 1. Overall, number of patients diagnosed with DM at the hospital increased rapidly from 16 in 2009 to 49 in 2012; p